Search for supersymmetric particles in light gravitino scenarios and sleptons NLSP - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alderweireld, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; et al. (2003)
A search for sleptons, neutralinos, charginos, sgoldstinos and heavy stable charged sleptons in the context of scenarios where the lightest supersymmetric particle is the gravitino, is presented. Data collected during 2000 with the DELPHI detector at centre-of-mass energies from 204 to 208 GeV were analysed and combined with all the data collected from 1995 to 1999 at lower energies. No evidence for the production of sleptons, neutralinos and charginos has been found, therefore new limits on the mass of these supersymmetric particles and on the model parameter space are set. The search for heavy stable charged sleptons also updates the stable sleptons mass limit. The absence of evidence for sgoldstino production allows limits to be set on its mass and on the scale of supersymmetry breaking.